Frequency of Atopic Diseases in Immunoglobulin A Deficiency - Nesli Ağralı; Seda Şirin Köse; Suna Asilsoy; Özden Anal (Galenos Publishing House, 2020)
INTRODUCTION: Selective IgA deficiency is the most common immunoglobulin disorder. While some patients are asymptomatic it has been also detected in patients with autoimmune and atopic disorders. In our study, we aimed to determine the relationship between Ig A deficiency and atopy and the prevalence of atopy in patients with IgA deficiency. METHODS: One hundred patients between the ages of 4 and 18, who were admitted to the Dokuz Eylül University Faculty of Medicine, Department of Pediatric Allergy, Department of Pediatric Gastroenterology and General Pediatric Outpatient Clinic, and whose IgA level was below -2 SD for any reason, were selected. Data was collected from hospital data management system retrospectively. A questionnaire including questions from International Study of Asthma and Allergies in Childhood (ISAAC) study, related to IgA deficiency and atopy is performed on phone with the parents. We aim to investigate association between Ig A deficiency and asthma, allergic rhinitis, eczema and food intolerance. RESULTS: Fifty-six (58.3%) patients were male and 40 (41.7%) were female. The mean age was 7.4 (+- 3.1). Twenty six percent of the patients had asthma, 7.3% had allergic rhinitis, 2.1% had drug allergy, 6.3% had eczema, 16.6% had urticaria, 9.4% had food allergy. Skin test and blood specific allergy tests were performed in 81.3% of our patients and allergen sensitivity was found 18.8%. DISCUSSION AND CONCLUSION: In children with Ig A deficiency, wheezing complaints in the past, asthma, atopic dermatitis, food allergy are more common in comparison with the results of the survey conducted in the normal population.